2010
DOI: 10.1016/j.ejca.2010.01.033
|View full text |Cite
|
Sign up to set email alerts
|

Loss of the CBX7 protein expression correlates with a more aggressive phenotype in pancreatic cancer

Abstract: Polycomb group (PcG) proteins function as multiprotein complexes and are part of a gene regulatory mechanism that determines cell fate during normal and pathogenic development. Several studies have implicated the deregulation of different PcG proteins in neoplastic progression. Pancreatic ductal adenocarcinoma is an aggressive neoplasm that follows a multistep model of progression through precursor lesions called pancreatic intraepithelial neoplasia (PanIN). Aim of this study was to investigate the role of PcG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
64
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(70 citation statements)
references
References 25 publications
5
64
0
1
Order By: Relevance
“…Much less is known about how the function and expression of the PRCs and their components are controlled. The regulation of CBX7 is particularly interesting because CBX7 is implicated in senescence (Gil et al ., 2004) and cancer (Bernard et al ., 2005; Scott et al ., 2007; Pallante et al ., 2008; Karamitopoulou et al ., 2010). In addition, CBX7 levels and consequently the composition of PRC1 complexes change dramatically during ES cell differentiation (Morey et al ., 2012; O'Loghlen et al ., 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Much less is known about how the function and expression of the PRCs and their components are controlled. The regulation of CBX7 is particularly interesting because CBX7 is implicated in senescence (Gil et al ., 2004) and cancer (Bernard et al ., 2005; Scott et al ., 2007; Pallante et al ., 2008; Karamitopoulou et al ., 2010). In addition, CBX7 levels and consequently the composition of PRC1 complexes change dramatically during ES cell differentiation (Morey et al ., 2012; O'Loghlen et al ., 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, in our series of breast tumors, we showed marked CBX7 underexpression and a nonexpected high positive link between ANRIL overexpression and CDKN2A/CDKNB/ARF overexpression, and more particularly with p14/ARF. Although these results seem to be contradictory, it can be hypothesized that CBX7 can exhibit both oncosuppressive and oncogenic functions, depending on type of cancer, microenvironment, and presence of interacting proteins (32)(33)(34)(35). CBX7 underexpression was strongly correlated with high SBR histologic grade, negative ERa and PR status, and EMT and breast cancer stem cell markers.…”
Section: Discussionmentioning
confidence: 91%
“…CBX7-knockout mice showed the development of lung and liver tumors accompanied by cyclin E up-regulation (4). Furthermore, some clinicopathologic studies have shown that CBX7 expression is inversely associated with the development of several human cancers, including bladder, pancreatic, and colon carcinomas (13)(14)(15). A recent study also implied a negative correlation between CBX7 expression and a malignant phenotype in human breast cancer (16).…”
Section: Discussionmentioning
confidence: 94%
“…In contrast, loss of CBX7 has been associated with increasing the malignancy grade in bladder, pancreatic, breast, gastric, and colon carcinomas (13)(14)(15)(16)(17), but its tumor suppression mechanism is unclear.…”
Section: /Esamentioning
confidence: 99%